Assessing patients’ knowledge about their management plan - Prasai, Neeti; Maskey, Himang Man Singh; Parajuli, Pravakar; Shakya, Namita (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Patients’ compliance for better health can be achieved if patients are well aware about their disease and treatment plan. Patient’s knowledge about diagnosis and treatment plan improves outcomes. This study aims to characterize patient’s knowledge about their hospital admission and treatment plan in different wards of Patan Hospital. Methods: This was a cross sectional study, undertaken in Patan Hospital. A pilot survey using purposive sampling was conducted to find out prevalence for the sample size (N=160) calculation and pre-testing of the questionnaire. Systematic random sampling was done. Finally, 154 patients agreed to be interviewed and data on their knowledge about treatment plan were analysed. The collected data were entered in Epi-Info (Free) and analysed in SPSS®. Results: Out of 154 patients interviewed, 118 (76.6% knew about their diagnosis and 48 (31.2%) were able to recall in medical terms. Regarding 151 patients who had undergone investigations, 60 (39.7%) patients knew details of at least one test, 7 (4.6%) knew details of all the tests, 41 (27.2%) knew about the results of their tests. Out of 143 patients who were prescribed medications, 100 (69.9%) patients were not able to state any of the medicines given to them and 8 (5.6%) were able to tell each of them. Conclusions: Most of our patient knew about their diagnosis and treatment plan; however, there are significant room for improvement in terms of educating patients about the tests being performed and drugs administered.